Numerical Method for Electromagnetic Wave Propagation Problem in a Cylindrical Inhomogeneous Metal Dielectric Waveguiding Structures - Smolkin, Eugene (Mathematical Modelling and Analysis, 2017)
The propagation of monochromatic electromagnetic waves in metal circular cylindrical dielectric waveguides filled with inhomogeneous medium is considered. The physical problem is reduced to solving a transmission eigenvalue problem for a system of ordinary differential equations. Spectral parameters of the problem are propagation constants of the waveguide. Numerical results are found with a projection method. The comparison with known exact solutions (for particular values of parameters) is made.